REMOTE SENSING FOR ENVIRONMENTAL SUSTAINABILITY: FROM OBSERVATION TO DECISION-MAKING - Huseynov, Mugabil (Collection of scientific papers «ΛΌГOΣ», 2025)
Remote sensing is based on the principle of collecting information about the Earth’s surface from a distance through electromagnetic radiation across different ranges of the spectrum. Active sensors transmit signals and measure their reflection, while passive sensors record natural radiation. In the fields of defense and environmental management, this technology enhances situational awareness, ensures the timeliness and objectivity of decision-making. Particularly under conditions of complex terrain along borderlines, as well as climatic and infrastructural constraints, a multi-layered architecture comprising satellites, unmanned aerial vehicles, and ground-based sensors becomes essential.